From Social Needs to the Functions of Management: Evolution of Operational Control (Economic journal of Lesya Ukrainka Volyn National University, 2016)
The article studies the historical development of operational control in the light of the evolution of the relationship between people and communities in different time period. Revealed that operational control has emerged as not understanding the needs of humanity and transformed into one of the main functions of management of enterprises. Its properties and specific characteristics manifest in practice since the beginning of the emergence and evolution of economic relations and the basis for other types and forms of control. Operational control should be considered a core (integral part) business and internal control including providing high quality of their.
Keywords: operational control, management, history, evolution and economic activity